Preparation method of biochar / titanium dioxide composite and photocatalytic application
By combining Ulta charcoal with titanium dioxide to form a biochar/titanium dioxide complex, the problem of low degradation efficiency of existing photocatalytic materials in marine environments is solved, and efficient photocatalytic degradation of oil pollutants is achieved.
Patent Information
- Application Number
- CN202211689848.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The existing photocatalytic materials have low degradation efficiency of petroleum pollutants in marine environments, and have a small adaptability range to light sources, poor stability, and it is difficult to effectively deal with dispersed oil pollution.
Biochar/titanium dioxide composite is used as the photocatalytic material, and the mixed crystal phase of the rutile phase and the anatase phase is formed by compositeing the Urothy carbon with titanium dioxide to improve the photocatalytic performance of the material.
High-efficiency photocatalytic degradation of soybean oil and diesel was achieved, with degradation rates reaching 72.35% and 67.69% respectively, significantly improving the photocatalytic performance and stability of the material.
Smart Images

Figure CN116212845B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic degradation of petroleum, and in particular to a preparation method and application of a biochar / titanium dioxide complex. Background Art
[0002] In the process of human development and utilization of the ocean, it is inevitable to pollute and damage the marine environment. Among them, marine oil pollution is one of the more serious marine pollution. When oil enters the seawater, a series of complex physical, chemical and biological reactions will occur, such as changing the color, transparency and other physical parameters of the seawater, hindering solar radiation from entering the seawater, affecting the photosynthesis of the water body, destroying water-gas exchange, deteriorating water quality, and affecting the growth of aquatic organisms, and causing harm to human health through the food chain. Therefore, it is very necessary to carry out research on efficient methods for removing oil pollutants.
[0003] At present, there are three commonly used methods for treating marine oil pollution: physical method, chemical method and biological method. The physical method is to use recovery devices such as pollution-cleaning ships, fences, and oil-absorbing materials to recover oil from the sea surface; the chemical method is to add chemical reagents such as emulsifiers, oil gelling agents, and sedimentation agents to the ocean or directly burn them to treat marine oil pollution; the biological method is to use biological catalysts to degrade and remove oil pollutants. These methods are often used to treat large amounts of oil pollution, and the treatment cost for dispersed oil pollution is high and the efficiency is low. The development of marine photochemistry provides a new way to clean up the ocean surface and soluble petroleum hydrocarbons. Under the irradiation of sunlight, the components in the water can absorb light energy under the action of photocatalysts and undergo corresponding photochemical reactions. In recent years, the use of nano-photocatalytic oxidation to degrade oil has attracted people's attention. This is a new type of heterogeneous chemical treatment method.
[0004] Studies have shown that high-energy nanoparticles after light absorption can catalyze the oxidation and degradation of petroleum pollutants, and can ultimately generate harmless or low-harm substances such as small molecules, CO2 and H2O, thereby achieving environmentally friendly treatment of pollutants. Nanomaterial photocatalytic oxidation has the advantages of utilizing clean solar energy for treatment, high reaction degradation efficiency, strong adaptability, and load recovery without secondary pollution, and has been used in basic research on the degradation of petroleum pollutants such as gasoline, diesel, organic hydrocarbons, and crude oil. Commonly used photocatalytic materials include oxides such as TiO2, ZnO, and SnO2, sulfides such as ZnS and CuS, and their composite materials. There have been many reports on the photocatalytic reactions of these materials, including theoretical analysis, calculation, and experimental verification. The main pathways of photocatalytic reactions include absorption of light energy, electron transition, catalytic adsorption of molecular reactions, generation of surface free radicals, and subsequent reactions.
[0005] At present, the main goal of catalytic material preparation is to effectively utilize solar energy by improving the effective photon efficiency and increasing the application spectrum width. The main methods include crystal selection, doping, deposition of precious metals, synthesis of heterojunctions (pn junctions, etc.), photosensitization, and synthesis of specific morphologies or structures. These studies have been widely reported in the degradation of conventional dyes, degradation of polycyclic aromatic hydrocarbons, treatment of volatile organic compounds, and treatment of petroleum-based water pollutants. However, compared with the application of photocatalytic materials in other fields, the basic and applied research on the photocatalytic degradation of petroleum pollutants in marine environments is generally less, and the theoretical research is insufficient. There are some common and characteristic problems that cannot be avoided, such as: (1) Most nano-semiconductor photocatalysts have low efficiency, unstable catalysis under light, and a small range of adaptability to light sources. In particular, there is little research under light conditions close to the natural environment of the ocean; (2) The composition, reaction conditions, and multiphase reaction process of marine pollutants in marine samples are more complex, which are different from conventional photodegradable organic matter. Petroleum hydrocarbons are more stable and their physical properties are also different from conventional pollutants.
[0006] Therefore, it is necessary to carry out systematic basic research work on the preparation, performance improvement, reaction testing, etc. of photocatalytic nanomaterials used in marine systems. In view of the current research status, the development of new carbon-based nano-photocatalytic material preparation and testing, and further research on the composite with new functional materials and inorganic / organic loading materials are technical problems that technicians in this field need to solve urgently. Summary of the invention
[0007] In view of this, the present invention provides a preparation method and application of a biochar / titanium dioxide composite.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing a biochar / titanium dioxide composite comprises the following steps:
[0010] (1) washing the Enteromorpha with water and ethanol three times in sequence, and then drying;
[0011] (2) carbonizing the dried Enteromorpha under an inert atmosphere to obtain Enteromorpha charcoal;
[0012] (3) Take a surfactant, concentrated hydrochloric acid, and anhydrous ethanol, and stir to mix evenly;
[0013] (4) Add titanyl sulfate to the solution of step (3), stir to mix evenly, and dry to obtain a uniform gel.
[0014] (5) Adding the Enteromorpha charcoal obtained in step (2) to the prepared gel, mixing evenly, and stirring at room temperature to obtain a mixed colloid.
[0015] (6) The obtained mixed colloid is calcined to obtain a titanium dioxide / entomomorpha charcoal composite.
[0016] Furthermore, the drying temperature in step (1) is 70-100° C., and the drying time is 8-24 hours.
[0017] Furthermore, in step (2), the carbonization temperature is 600-900° C., and the carbonization time is 2-8 hours.
[0018] Furthermore, in step (3), the surfactant is surfactant F127, and the mass fraction of concentrated hydrochloric acid is 36-38%;
[0019] The ratio of the mass of the surfactant to the volume of concentrated hydrochloric acid and the volume of anhydrous ethanol is 1-3g:20-30ml:40-80ml.
[0020] Furthermore, in step (3), the stirring rate is 400-1600 r / min, and the stirring time is 1-8 h.
[0021] Furthermore, the mass ratio of the volume of titanyl sulfate to F127 in step (4) is 5-10 ml: 1-3 g.
[0022] Furthermore, in step (4), the stirring rate is 400-1600 r / min, and the stirring time is 1-8 h;
[0023] The drying temperature is 60-80° C., and the drying time is 6-12 hours.
[0024] Furthermore, the volume ratio of the mass of the Enteromorpha charcoal to the titanyl sulfate in step (5) is 0.4-1 g: 5-10 ml;
[0025] The stirring rate is 400-1600 r / min, and the stirring time is 8-24 h.
[0026] Furthermore, in step (6), the calcination temperature is 400-650° C., and the calcination time is 1-6 hours.
[0027] The beneficial effect of the present invention is that the present invention discloses a preparation method of a biochar-loaded titanium dioxide complex and its application in photocatalytic degradation of petroleum. The present invention uses marine biomass Enteromorpha as a carbon source, after washing and drying, carbonizing under high temperature conditions, and then treating with dilute hydrochloric acid to obtain a biochar carrier, and then introducing a titanium source, using a hydrothermal method, preparing a complex of titanium dioxide and biochar, and studying its photocatalytic degradation performance of oil pollutants. The results show that the biochar / titanium dioxide material provided by the present invention, in which the titanium dioxide is a mixed crystal phase of rutile phase and anatase phase, takes 0.05g soybean oil as the degradation target, disperses it in 50ml water, and adds 50mg of the prepared biochar / titanium dioxide complex, under normal temperature conditions, the degradation rate of oil reaches 72.35% after 12 hours of degradation; takes 0.03g diesel as the degradation target, disperses it in 50ml water, and adds 50mg of the prepared biochar / titanium dioxide complex, under normal temperature conditions, the degradation rate of oil reaches 67.69% after 10 hours of degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the XRD pattern of the biochar / titanium dioxide composite prepared in Example 1 of the present invention;
[0029] Figure 2 This is a transmission electron microscopy image of the biochar / titanium dioxide composite prepared in Example 1 of the present invention;
[0030] Figure 3 Transmission electron microscopy and corresponding mapping diagram of the biochar / titanium dioxide composite prepared in Example 1 of the present invention;
[0031] Figure 4 This is the element distribution diagram of the biochar / titanium dioxide composite prepared in Example 1 of the present invention;
[0032] Figure 5 This is a Raman spectrum of the biochar / titanium dioxide composite prepared in Example 1 of the present invention;
[0033] Figure 6 This is the XPS spectrum of the biochar / titanium dioxide composite O1s prepared in Example 1 of the present invention;
[0034] Figure 7 This is the XPS spectrum of the biochar / titanium dioxide composite Ti2p prepared in Example 1 of the present invention;
[0035] Figure 8 The UV absorption spectra of the biochar / titanium dioxide complex prepared in Example 1 of the present invention degrading soybean oil at different times;
[0036] Fig. 9This is a schematic diagram of the time and concentration of photolysis of soybean oil by the biochar / titanium dioxide composite prepared in Example 1 of the present invention;
[0037] Fig.10 The UV absorption spectra of the biochar / titanium dioxide composite prepared in Example 1 of the present invention when degrading diesel at different times;
[0038] Fig.11 Schematic diagram of the time and concentration of photolysis of diesel by the biochar / titanium dioxide composite prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] A method for preparing a biochar / titanium dioxide composite:
[0042] (1) Wash the Enteromorpha with water and ethanol three times, and then dry at 85°C for 18 h;
[0043] (2) carbonizing the dried Enteromorpha at 750° C. for 5 h under an inert atmosphere to obtain Enteromorpha charcoal;
[0044] (3) Take 2g F127, 25ml 36% concentrated hydrochloric acid, and 60ml anhydrous ethanol, and stir at 1000r / min for 5h;
[0045] (4) Add 8 ml of titanyl sulfate to the solution of step (3), stir and mix at 900 r / min for 6 h, and dry at 70° C. for 9 h to obtain a uniform gel.
[0046] (5) Add 0.7 g of Enteromorpha charcoal to the prepared gel and mix evenly. Stir at room temperature at 1000 r / min for 16 h to obtain a mixed colloid.
[0047] (6) The obtained mixed colloid was calcined at 500°C for 3 h to obtain a titanium dioxide / entomomorpha charcoal composite.
[0048] As shown in the XRD diagram of Example 1. It can be clearly seen from the figure that the peaks at 25.3°, 36.9°, 37.8°, 48.0°, 53.9°, 55.0°, 62.7°, 68.8°, 70.3°, and 75.0° are diffraction peaks of anatase titanium dioxide (101), (103), (004), (200), (105), (211), (204), (116), (220), and (215) crystal planes, respectively. The peaks at 27.4 and 36.1 are diffraction peaks of rutile phase titanium dioxide (110) and (101) crystal planes. The peak at 26.5 is the diffraction peak of graphite (002) crystal plane. This shows that after the prepared biochar is loaded, the generated titanium dioxide is a mixed crystal phase of anatase phase and rutile phase.
[0049] Attached Figure 2 , are transmission electron microscopy images of Example 1. From Figure A, it can be clearly seen that the nanoparticles are distributed on the carbon substrate. Figure B shows that the diameter of the nanoparticles is about 10-15 nanometers, the particle size is relatively uniform and evenly dispersed on the biochar carrier. From high-resolution electron microscopy images C and D, it can be seen that the clear lattice fringes of the nanoparticles are intertwined.
[0050] Attached Figure 3 , is the transmission electron microscopy of Example 1 and the corresponding mapping picture. From the figure, it can be clearly seen that C, N, O, and Ti elements are evenly distributed on the carbon substrate, and N nitrogen element is doped in the biochar, and the N element comes from biomass.
[0051] Attached Figure 4 , is the element distribution diagram of Example 1. The distribution of four elements can be seen from the diagram, among which the atomic ratios of C, N, O, and Ti are 38.10%, 15.44%, 30.89%, and 15.57%, and the atomic ratio of Ti and O is about 2:1.
[0052] Attached Figure 5 , is the Raman spectrum of Example 1. It can be seen from the figure that the -1 and 1580cm -1 The characteristic peaks of carbon D band and G band are located at 422cm -1 and 608cm -1 The peak is the vibration peak of rutile phase titanium dioxide, located at 139cm -1 and 255cm -1 The peaks are characteristic peaks of anatase phase titanium dioxide. This indicates that the method successfully composites titanium dioxide and biochar, and the titanium dioxide is a mixed crystal of rutile and anatase phases.
[0053] Attached Figure 6The XPS spectrum of O1s shows that the peak at 530.2 eV is the peak of titanium dioxide lattice oxygen, the peak at 531.0 eV is the peak of oxygen defect, and the peak at 532.4 eV is the peak of oxygen adsorbed on the surface of the material, such as O 2- , O 2- , O - , OH - The peak.
[0054] Attached Figure 7 This is the XPS spectrum of Ti2p. It can be seen from the figure that 458.9eV, 464.6eV, and 472.2eV correspond to Ti2p 3 / 2 , Ti2p 1 / 2 and Satellite Peak.
[0055] Attached Figure 8 The UV absorption spectra of soybean oil degradation at different times show that the absorbance of the target degradation product gradually decreases with the increase of time, proving that the synthesized Enteromorpha charcoal / titanium dioxide complex can effectively degrade oil.
[0056] Attached Fig. 9 The line graph of photolysis time and soybean oil concentration shows that the absorbance of the target degradation product decreases gradually with the increase of time. After 12 hours of photodegradation, the oil concentration increases from the initial 79.12 mg / L to -1 Reduced to 21.88 mgL -1 The degradation rate reached 72.35%, proving that the synthesized composite material has good photocatalytic ability to degrade oil.
[0057] Attached Fig.10 The UV absorption spectra of diesel degradation at different times show that the absorbance of the target degradation product gradually decreases with the increase of time, proving that the synthesized Enteromorpha charcoal / titanium dioxide complex can effectively degrade diesel.
[0058] Attached Fig.11 The line graph of photolysis time and diesel concentration shows that the absorbance of the target degradation product decreases gradually with the increase of time. After 8 hours of photodegradation, the oil concentration decreases from the initial 45.25 mg / L -1 Reduced to 14.62 mgL -1 The degradation rate reached 67.69%, proving that the synthesized composite material has good photocatalytic ability to degrade oil.
[0059] Example 2
[0060] A method for preparing a biochar / titanium dioxide composite:
[0061] (1) Wash the Enteromorpha with water and ethanol three times, and then dry at 100°C for 8 h;
[0062] (2) carbonizing the dried Enteromorpha at 900° C. for 2 h under an inert atmosphere to obtain Enteromorpha charcoal;
[0063] (3) Take 1g F127, 30ml 36% concentrated hydrochloric acid, and 40ml anhydrous ethanol, and stir at 1600r / min for 1h;
[0064] (4) Add 5 ml of titanyl sulfate to the solution of step (3), stir and mix at 400 r / min for 8 h, and dry at 80° C. for 6 h to obtain a uniform gel.
[0065] (5) Add 0.4 g of Enteromorpha charcoal to the prepared gel and mix evenly. Stir at room temperature at 1600 r / min for 8 h to obtain a mixed colloid.
[0066] (6) The obtained mixed colloid was calcined at 400°C for 6 hours to obtain a titanium dioxide / entomomorpha charcoal composite.
[0067] Example 3
[0068] A method for preparing a biochar / titanium dioxide composite comprises the following steps:
[0069] (1) Wash the Enteromorpha with water and ethanol three times, and then dry at 70°C for 24 h;
[0070] (2) carbonizing the dried Enteromorpha at 600° C. for 8 h under an inert atmosphere to obtain Enteromorpha charcoal;
[0071] (3) Take 3g F127, 20ml 37% concentrated hydrochloric acid, and 80ml anhydrous ethanol, and stir at 400r / min for 8h;
[0072] (4) Add 10 ml of titanyl sulfate to the solution of step (3), stir and mix at 1600 r / min for 1 h, and dry at 60° C. for 12 h to obtain a uniform gel.
[0073] (5) Add 1 g of Enteromorpha charcoal to the prepared gel and mix evenly. Stir at room temperature at 400 r / min for 24 h to obtain a mixed colloid.
[0074] (6) The obtained mixed colloid was calcined at 650°C for 1 h to obtain a titanium dioxide / entomomorpha charcoal composite.
[0075] Example 4
[0076] A method for preparing a biochar / titanium dioxide composite comprises the following steps:
[0077] (1) Wash the Enteromorpha with water and ethanol three times, and then dry at 80°C for 12 h;
[0078] (2) carbonizing the dried Enteromorpha at 700° C. for 4 h under an inert atmosphere to obtain Enteromorpha charcoal;
[0079] (3) Take 3g F127, 22ml 38% concentrated hydrochloric acid, and 50ml anhydrous ethanol, and stir at 1000r / min for 3h;
[0080] (4) Add 8 ml of titanyl sulfate to the solution of step (3), stir and mix at 1200 r / min for 4 h, and dry at 65° C. for 10 h to obtain a uniform gel.
[0081] (5) Add 0.6 g of Enteromorpha charcoal to the prepared gel and mix evenly. Stir at room temperature at 800 r / min for 20 h to obtain a mixed colloid.
[0082] (6) The obtained mixed colloid was calcined at 450°C for 5 h to obtain a titanium dioxide / entomomorpha charcoal composite.
[0083] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. Application of a biochar / titanium dioxide composite in photocatalytic degradation of oil pollutants, characterized in that: The preparation method of the biochar / titanium dioxide complex is: (1) Wash the Enteromorpha with water and ethanol three times in sequence, and then dry it; (2) carbonizing the dried Enteromorpha in an inert atmosphere to obtain Enteromorpha charcoal; the carbonization temperature is 600-900° C., and the carbonization time is 2-8 hours; (3) Take F127, concentrated hydrochloric acid and anhydrous ethanol, stir and mix them evenly; the surfactant is surfactant F127, the mass fraction of the concentrated hydrochloric acid is 36-38%; the mass ratio of the surfactant to the volume of concentrated hydrochloric acid and the volume of anhydrous ethanol is 1-3g:20-30ml:40-80ml; (4) adding titanyl sulfate to the solution of step (3), stirring to mix evenly, and drying to obtain a uniform gel, wherein the mass ratio of the titanyl sulfate to F127 is 5-10 ml: 1-3 g; (5) adding the Enteromorpha charcoal obtained in step (2) to the prepared gel, mixing evenly, and stirring at room temperature to obtain a mixed colloid, wherein the mass ratio of the Enteromorpha charcoal to the volume ratio of titanyl sulfate is 0.4-1 g: 5-10 ml; (6) The obtained mixed colloid is calcined to obtain a titanium dioxide / entomomorpha charcoal composite.
2. The use of a biochar / titanium dioxide composite in photocatalytic degradation of oil pollutants according to claim 1, characterized in that: The drying temperature in step (1) is 70-100°C and the drying time is 8-24h.
3. The use of a biochar / titanium dioxide composite in photocatalytic degradation of oil pollutants according to claim 1, characterized in that: The stirring rate in step (3) is 400-1600 r / min, and the stirring time is 1-8 h.
4. The use of a biochar / titanium dioxide composite in photocatalytic degradation of oil pollutants according to claim 1, characterized in that: The stirring rate in step (4) is 400-1600 r / min, and the stirring time is 1-8 h; The drying temperature is 60-80° C., and the drying time is 6-12 hours.
5. The use of a biochar / titanium dioxide composite in photocatalytic degradation of oil pollutants according to claim 1, characterized in that: The stirring rate in step (5) is 400-1600 r / min, and the stirring time is 8-24 h.
6. The use of a biochar / titanium dioxide composite in photocatalytic degradation of oil pollutants according to claim 1, characterized in that: The calcination temperature in step (6) is 400-650°C, and the calcination time is 1-6h.
Citation Information
Patent Citations
Preparation method of biomimetic synthesis activated carbon-titanium dioxide composite material
CN112354533A
Preparation method and application of mixed crystal type titanium dioxide photocatalyst
CN113198441A